Stromal CD10 expression in invasive breast carcinoma - Haval D. Ali; Jalal A. Jalal; Ava T. Ismail; Wahda MT. Alnuaimy (Zanco Journal of Medical Sciences, 2018)
Background and Objective: This study aimed to assess the immunohistochemical expression of stromal CD10 in invasive breast carcinoma and determine its relationship with some clinicopathological parameters.